Gender and adaptive collaborative management in forested Ugandan landscapes - Bomuhangi, A.; Banana, A.Y.; Bushoborozi, Jimmy; Mukasa, C.M.; Tibazalika, A.; Mwangi, E. (Routledge, 2021)
Forestry management in Uganda has traditionally been a masculine field, although recent years have seen a number of changes in such management. With the introduction of participatory approaches such as adaptive collaborative management (ACM) and collaborative forest management (CFM), today, women more commonly own forest and work in the forestry sector. Despite this, the degree of women’s involvement remains low in comparison to their male counterparts. In order to address this gender gap, this chapter examines three questions: (1) what determines men’s and women's participation in forest management under different forest management approaches? (2) How do men and women rate their quality of participation in forest management in public or private forestry spaces? (3) What do women and men harvest from the forest and how do they use the income earned from the sale of forest products? To answer these questions data were collected from a nationwide intra-household survey from 1052 respondents across four agro-ecological zones, under multiple forest tenure regimes. The analyses show that the gender gap in participation and representation in community forestry in Uganda was minimized in communities where ACM was being implemented. The study recommends that forest adjacent communities should 1) enter into participatory forest management arrangements with the forest owners/managers (national forest authority, local government or private forest owners) or 2) be facilitated to form tree-planting groups or associations by NGOs and local government forestry officials, as a means to increase women’s participation in forestry.